2014
DOI: 10.1021/jp510180j
|View full text |Cite
|
Sign up to set email alerts
|

Extended Y-Rule Method for the Characterization of the Aromatic Sextets in Cata-Condensed Polycyclic Aromatic Hydrocarbons

Abstract: The location, number, and migrating behavior of the sextets in the cata-condensed benzenoid polycyclic aromatic hydrocarbons with available bay regions have been determined by a new proposed topological methodology called the extended Y-rule. The precursor of this rule is the well-known Y-rule method for determining sextets in peri-condensed polycyclic aromatic hydrocarbons. The new methodology has been successfully validated by means of literature information and by theoretical nucleus independent chemical sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 60 publications
0
32
0
Order By: Relevance
“…The smaller E g and ΔEL in TDI, as compared with NDI or PDI, are conducive to higher electronic conductivity as well as higher operating voltages during the charge–discharge processes. Additionally, aromatic compounds with the highest ratio of sextets are the most stable ones according to Clar's rule, [ 31 ] and thus, it was found that TDI possesses the highest ratio of sextets after the two electrons reduction, as compared to PDI and NDI. Apparently, these factors significantly affect the storage electron capability of electrode materials.…”
Section: Principles Of Aromatic Imide Electrode Materialsmentioning
confidence: 99%
“…The smaller E g and ΔEL in TDI, as compared with NDI or PDI, are conducive to higher electronic conductivity as well as higher operating voltages during the charge–discharge processes. Additionally, aromatic compounds with the highest ratio of sextets are the most stable ones according to Clar's rule, [ 31 ] and thus, it was found that TDI possesses the highest ratio of sextets after the two electrons reduction, as compared to PDI and NDI. Apparently, these factors significantly affect the storage electron capability of electrode materials.…”
Section: Principles Of Aromatic Imide Electrode Materialsmentioning
confidence: 99%
“…They are the most aromatic centers in PAHs and indicate regions of local aromaticity in large molecules. , Consistent with the stability of aromatic rings resulting from electron delocalization, AS contribute to the kinetic stability of PAHs by increasing the HOMO–LUMO gap . IDB, on the other hand, have polyene-like character and can be as reactive as olefinic double bonds in unconjugated molecules. ,, The most probable electronic structure of a PAH is one in which the number of AS is maximized while the number of IDB is minimized, and algorithms such as the Y-rule have been developed to identify these electronic structures. , …”
Section: Results and Discussionmentioning
confidence: 99%
“…Of course, the dependency of the local aromaticity in polycyclic conjugated systems on the annelation manner -linear or angular -is not a new finding since the influence of annelation manner on the local aromaticity in benzenoid and nonbenzenoid polycyclic compounds have been studied in many recent papers. [92][93][94][95][96][97][98][99] Now, an interesting question is whether further annelation of the central benzene ring of 7 and 3 in the angular position by four-and six-membered ring, respectively, will increase the local aromaticity of the rings in these new compounds?…”
Section: Cyclobutadieno-annelated Benzenementioning
confidence: 99%